The evolution of the mood of the Izhevsk-Votkinsk workers in October 1917–December 1918 - N. A. Zayats (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the problem of determining the views of Izhevsk-Votkinsk workers in 1917–1918, which led them to participate in the anti-Soviet uprising of 1918. The purpose of the study is to revise previous ideas about this subject and obtain reliable scientific knowledge about the moods and interests of the population of Izhevsk and Votkinsk in 1918. Based on the developments of historiography, as well as archival sources introduced into scientific circulation, it is established that the mood of the workers at these factories is determined by material and personal interests, characterized by patriarchy and weak politicization, the popularity of the moderate slogans of the Constituent Assembly and non-participation in the war. In conclusion, it is emphasized that the weak formalization of the workers’ sentiments and the apoliticalism of most of them allowed first the Bolsheviks, and then their opponents, to establish themselves in power, but the indifference of the majority of workers in both cases weakened the position of the authorities.